EFEKTIVITAS PENGGUNAAN MEDIA JEJARING SOSIAL FACEBOOK TERHADAP KEGIATAN KOMUNIKASI UNIVERSITAS DI JAKARTA - Oktafalia Marisa (Business Management Journal, 2017)
Social networking is a phenomenon in Indonesia, almost all communities have and actively use an account at social networking. The phenomenon has changed the initial function of social networking.Many activities carried out through social networking. Facebook, with a number of accessor, turns out to encourage universities in Indonesia to take part in utilizing this social networking. Almost all universities have an official account to accommodate their activities. This research took the Bunda Mulia University, STIE Trisakti and, Tarumanagara University as samples to conduct research on the effectiveness of communication activities facebook universities in Indonesia. The results shown us, facebook was considered effective as a means of communication for students Key Words:Social Media, communication, and Effectivity